2014
DOI: 10.4236/fns.2014.53035
|View full text |Cite
|
Sign up to set email alerts
|

The Principles of Starch Gelatinization and Retrogradation

Abstract: The polysaccharides, such as κ-carrageenan, ι-carrageenan, agarose (agar), gellan gum, amylose, curdlan, alginate, and deacetylated rhamsan gum, in water changed into an ice-like structure with hydrogen bonding between polymer and water molecules, and between water-water molecules even at a concentration range of 0.1%-1.0% (W/V) at room temperature, resulting in gelation. Such dramatic changes from liquid into gels have been understood at the molecular level in principles. In this review, we describe the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
97
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 51 publications
1
97
0
7
Order By: Relevance
“…According to Santana et al (2014), starch is a macro-constituent of many foods and is widely consumed by humans as an inexpensive and stable carbohydrate source. It is useful in food production, cosmetics, paper, textile, as adhesive, thickening, stabilizing, stiffening and gelling agents (Tako et al, 2014). Thys et al (2013) also reported starch as the most common thickening and gelling agent used by the food industry in the development of a large number of products such as soups, sauces, and ready-to-eat food among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Santana et al (2014), starch is a macro-constituent of many foods and is widely consumed by humans as an inexpensive and stable carbohydrate source. It is useful in food production, cosmetics, paper, textile, as adhesive, thickening, stabilizing, stiffening and gelling agents (Tako et al, 2014). Thys et al (2013) also reported starch as the most common thickening and gelling agent used by the food industry in the development of a large number of products such as soups, sauces, and ready-to-eat food among others.…”
Section: Introductionmentioning
confidence: 99%
“…Starch is one of the most important polysaccharides found in many food plants and consists of amylose and branched amylopectin molecules (Tako et al, 2014). According to Santana et al (2014), starch is a macro-constituent of many foods and is widely consumed by humans as an inexpensive and stable carbohydrate source.…”
Section: Introductionmentioning
confidence: 99%
“…Eduardo et al [7] found that composite bread with a combination of hydrocolloids and emulsifiers had the lowest crumb firmness ( < 0.05), significantly reduced melting enthalpy values compared to the reference bread, and delayed melting of recrystallized amylopectin enthalpy. The antiretrogradation effect of emulsifiers depends on the ratio of amylose and amylopectin in starch [2,8]. In addition, the rice storage temperature, the water content, and other factors will also influence the result of emulsifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Starch retrogradation is a process whereby when a gelatinized solution is cooled for a long time, it changes into a gel and rearranges itself into a crystalline structure. It is an unavoidable phenomenon affecting the texture and quality of many ready meals, including starchy rice foods [2,3]. Starch retrogradation severely affects the nutritional properties and storage stability of these products, seriously limiting the development of the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there are some basic thermodynamic and theoretical rules in gel-formation processes of polysaccharides including water molecules in principle [25][26][27]. The green seaweed, Monostroma nitidum, is widespread in nature between Korea, China and Japan.…”
Section: Introductionmentioning
confidence: 99%